Application of oil palm empty fruit bunch composite as an eco-efficient product - Mohd Jalani, M.F (Universiti Malaysia Sarawak, UNIMAS, 2008)
In this project the main idea is to propose a different type of material in usage of producing a product. The different type that is mention in this project is natural composite. This innovation can be called an act on satisfying the changing needs of society, in means of efficient, economical and environmental. Eco-efficient can be suitable in describing those aspects. In this study the evaluation of relationship between natural composite and eco-design product towards environmental is conducted. The result of each of those entities can construct a new mean of environmental product. Natural composite is done by combining two elements which is natural waste and polyester for this particular research. Oil palm empty fruit bunch fiber is a common waste that is increasing in Malaysia agricultural region. From the analysis and the study of design for environment, it shown that the quality of oil palm empty fruit bunch fiber composite can be used for designing an eco-efficient product. In the design process, evaluation is conducted using axiomatic design application. The result for the second level of FR1 is uncoupled design matrix, FR2 decoupled design matrix and FR3 uncouple design matrix. Results of the design satisfied both customer requirement and DFE (design for environmental). End product for this project is eco-cooler pad. The product is an efficient design with added environmental aspect, can be reuse, remanufactured and no waste is involved during the process and after life span.